Pola Terapi pada pasien Kanker Servik di RSUD Prof. Dr. Margono Soekardjo, Purwokerto - Alfiyah, Hasani Siti; Setiawan, Didik; Soedarso, . (Indonesian Research Gateway)
The morbidity and mortality of cervical cancer is high in the world. To improve the outcome of cervical cancer therapy, an appropriate approach should be given to the patients. The study purpose was to describe the pattern of treatment in cervical cancer patients in Prof. Dr. Margono Soekardjo Public Hospital. A cross sectional descriptive study was done in 150 patients data which was collected from patients medical records. The patterns of treatment in cervical cancer patients of Prof. Dr. Margono Soekardjo Public Hospital was dissection therapy 0.67% in stadium III-IIIB, radiotheraphy 59.32 % in stadium II-IVB, chemotherapy 12.0% in stadium III-IIB and chemoradiation 10.01% in stadium I-IIIB. Many of chemotherapy drugs given to cervic cancer were the combination of cisplatin-doksorubisin-siklofosfamid in 66.6% and attached diseases were anemia 66.29%. Conclussion, most of cervical cancer patients in Prof. Dr. Margono Soekardjo Public Hospital was treated with radiotherapyKeywords : cervic cancer, patterns treatment, stadium